A Rare Presentation of Extraosseous Ewing Sarcoma Manifesting as a Dumbbell Tumor on the Nape of the Neck - Abrar A. AlAtwan; Mousa Behbehani; Ali Sayed Ali (Case Reports in Surgery)
Ewing sarcoma is a rare poorly differentiated and highly malignant tumor primarily affecting the skeletal system. It most commonly presents during the first two decades of life and rarely might it be of extraskeletal origin. Majority of extraskeletal cases are reported in the paravertebral and lower limb, with very few cases reported in the cervical spine region. We report a case of extraskeletal Ewing sarcoma in a 42-year-old man who presented with a 1-year history of neck swelling associated with neck pain, diagnosed by computed tomography and magnetic resonance imaging scans, in conjunction with histological analysis. Very few cases of cervical EES presenting as dumbbell tumors have been documented in the literature especially in this age group.